(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
We have prepared the complexes RhCl(dppe), RhCl(dppp) and RhCl(dppb), where dppe = diphenylphosphinoethane; dppp = diphenylphosphinopropane; dppb = diphenylphosphinobutane. The above complexes were used as catalytic precursor in the hydroformylation of camphene at diferents concentrations and temperatures. It has found that the best catalytic precursor was the Rhodium complex with dppp as ligand it seems that the P-Rh-P angle is very important in substrate activation.